Pharmacological interventions for treating chronic prostatitis/chronic pelvic pain syndrome - Franco, Juan VA (Cochrane Database Syst Rev, 2019)
BACKGROUND: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common disorder in which the two main clinical features are pelvic pain and lower urinary tract symptoms. There are currently many approaches for its management, using both pharmacological and non‐pharmacological interventions. The National Institute of Health ‐ Chronic Prostatitis Symptom Index (NIH‐CPSI) score is a validated measure commonly used to measure CP/CPPS symptoms. We considered a 25% decrease of NIH‐CPSI baseline score or a six‐point reduction as MCID. OBJECTIVES: To assess the effects of pharmacological therapies for chronic prostatitis/chronic pelvic pain syndrome. SEARCH METHODS: We performed a comprehensive search using CENTRAL, MEDLINE, Embase, PsycINFO, CINAHL, trial registries, grey literature and conference proceedings, with no restrictions on the language of publication or publication status. The date of the latest search of all databases was July 2019. SELECTION CRITERIA: We included randomised controlled trials. Inclusion criteria were men with a diagnosis of CP/CPPS. We included all available pharmacological interventions compared to placebo or in head‐to‐head comparisons. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed study eligibility, extracted data, and assessed the risks of bias of included studies. We assessed the quality of the evidence (QoE) using the GRADE approach. MAIN RESULTS: We included 99 unique studies in 9119 men with CP/CPPS, with assessments of 16 types of pharmacological interventions. Unless stated otherwise, our comparisons were based on short‐term follow‐up (less than 12 months). Most studies did not specify their funding sources; 21 studies reported funding from pharmaceutical companies. 1. Alpha blockers: (24 studies, 2061 participants). We are uncertain about the effects of these drugs on prostatitis symptoms when compared to placebo at short‐term follow‐up (mean difference (MD) in total NIH‐CPSI score −5.01, 95% confidence interval (CI) −7.41 to −2.61; 18 studies, 1524 participants, very low QoE) and at long‐term follow‐up (MD −5.60, 95% CI −10.89 to −0.32; 4 studies, 235 participants, very low QoE). Alpha blockers may be associated with an increased incidence of adverse events, such as dizziness and postural hypotension (risk ratio (RR) 1.60, 95% CI 1.09 to 2.34; 19 studies, 1588 participants; low QoE). Alpha blockers probably result in little to no difference in sexual dysfunction, quality of life and anxiety and depression (moderate to low QoE). 2. 5‐alpha reductase inhibitors (5‐ARI): (2 studies, 177 participants). Finasteride probably reduces prostatitis symptoms compared to placebo (NIH‐CPSI score MD −4.60, 95% CI −5.43 to −3.77; 1 study, 64 participants; moderate QoE) and may not be associated with an increased incidence of adverse events (low QoE). There was no information on sexual dysfunction, quality of life or anxiety and depression. 3. Antibiotics: (6 studies, 693 participants). Antibiotics (quinolones) may reduce prostatitis symptoms compared to placebo (NIH‐CPSI score MD −2.43, 95% CI −4.72 to −0.15; 5 studies, 372 participants; low QoE) and are probably not associated with an increased incidence in adverse events (moderate QoE). Antibiotics probably result in little to no difference in sexual dysfunction and quality of life (moderate QoE). There was no information on anxiety or depression. 4. Anti‐inflammatories: (7 studies, 585 participants). Anti‐inflammatories may reduce prostatitis symptoms compared to placebo (NIH‐CPSI scores MD −2.50, 95% CI −3.74 to −1.26; 7 studies, 585 participants; low QoE) and may not be associated with an increased incidence in adverse events (low QoE). There was no information on sexual dysfunction, quality of life or anxiety and depression. 5. Phytotherapy: (7 studies, 551 participants). Phytotherapy may reduce prostatitis symptoms compared to placebo (NIH‐CPSI scores MD −5.02, 95% CI −6.81 to −3.23; 5 studies, 320 participants; low QoE) and may not be associated with an increased incidence in adverse events (low QoE). Phytotherapy may not improve sexual dysfunction (low QoE). There was no information on quality of life or anxiety and depression. 6. Botulinum toxin A (BTA): Intraprostatic BTA injection (1 study, 60 participants) may cause a large reduction in prostatitis symptom (NIH‐CPSI scores MD −25.80, 95% CI −30.15 to −21.45), whereas pelvic floor muscle BTA injection (1 study, 29 participants) may not reduce prostatitis symptoms (low QoE). Both comparisons used a placebo injection. These interventions may not be associated with an increased incidence in adverse events (low QoE). There was no information on sexual dysfunction, quality of life or anxiety and depression. 7. Allopurinol: (2 studies, 110 participants). Allopurinol may result in little to no difference in prostatitis symptoms and adverse events when compared to placebo (low QoE). There was no information on sexual dysfunction, quality of life or anxiety and depression. 8. Traditional Chinese medicine (TCM): (7 studies, 835 participants); TCM may reduce prostatitis symptoms (NIH‐CPSI score, MD ‐3.13, 95% CI ‐4.99 to ‐1.28; low QoE) and may not be associated with an increased incidence in adverse events (low QoE). TCM probably does not improve sexual dysfunction (moderate QoE) and may not improve symptoms of anxiety and depression (low QoE). There was no information on quality of life. The most frequent reasons for downgrading the QoE were study limitations, inconsistency and imprecision. We found few trials with active comparators. AUTHORS' CONCLUSIONS: We found low‐ to very low‐quality evidence that alpha blockers, antibiotics, 5‐ARI, anti‐inflammatories, phytotherapy, intraprostatic BTA injection, and traditional Chinese medicine may cause a reduction in prostatitis symptoms without an increased incidence of adverse events in the short term, except for alpha blockers which may be associated with an increase in mild adverse events. We found few trials with active comparators and little evidence of the effects of these drugs on sexual dysfunction, quality of life or anxiety and depression. Future clinical trials should include a full report of their methods, including adequate masking, consistent assessment of all patient‐important outcomes, including potential treatment‐related adverse events, and appropriate sample sizes.